KAJIAN UMAT TERHADAP SELAMETAN KELAHIRAN DALAM TRADISI JAWA (STUDI KASUS DI GEREJA SAMBIROTO) - Evita Irene Pintubatu; Anselmus Joko Prayitno; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
Traditions that already live in com-munities are not all based on religious teach-ings. Some traditions have disagreements that conflict with religious teachings. Humans as moral beings are required to act intelligently in response to tradition and religion. The attitude of the people of the Sambiroto Church demonstrates mutual respect for and ac-ceptance of the implementation of the ful-filling of the birth held within the confines of the Sambiroto Church. Involvement and par-ticipation in the carrying out of the womb strengthen the relationship between neighbor and Lord. The study aims to examine the atti-tudes of the people, relevance, and views of the Sambiroto Church on the birth anniver-sary. The study USES a descriptive quantita-tive approach. The subject of this study is par-ish priest, deacon, and ward leader. Data col-lection techniques using angkets, interviews, and documentation. The people's review of the anniver-sary of birth in the Sambiroto Church is linked to the attitudes of the people reaching 48%. The results indicate a positive response to the birth in the Sambiroto Church. Relevance of birth length scores 72%. This result indicates that meras still have relevance for birth. The Sambiroto Church's view scored 56%. The result indicates that the Church of Sambiroto accepted the traditions of the people and helped to approach the traditions of the Cath-olic faith. In view of the results of this study, both the parish and the parish priests respond-ed.